The Influence Of Project Based Learning, Learning Outcomes And Gender In Learning Sport Physical And Health (PJOK) In Schools - Eddy Marheni; Nina Jermaina; Eko Purnomo (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
This study aims to determine the learning outcomes of PBL method with conventional methods and especially gender. This research was conducted at SMAN 12 Sijunjung. The research was carried out as much as 2x45 minutes according to the lesson hours. This type of research is Quasi Experiment Research or quasi-experimental. The main object in this study were male and female students in SMAN 12 Sijunjung. The results showed that with the application of problem-based learning (PBL) children would become more active, creative and innovative in learning PJOK, and create equal understanding and interest in PJOK subjects. To improve the quality of learning more effectively, the teacher must better understand the PJOK learning strategy.